2022
DOI: 10.1002/osp4.585
|View full text |Cite
|
Sign up to set email alerts
|

Examining weekly facilitated group sessions and counselor‐crafted self‐monitoring feedback on treatment outcome in digital weight control: A pilot factorial study

Abstract: Objective Weight control programs that incorporate group sessions produce greater weight losses, but this has not been explored in the context of online programs. Further, counselor‐crafted self‐monitoring feedback is a core element of lifestyle interventions, although pre‐scripted, modular feedback which does not require detailed counselor review may adequately promote weight loss. The current study explored the weight losses achieved in an online program that included facilitated group sessions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…A recent pilot study that used a 2 × 2 factorial design provides some insights into FB (counselor-crafted vs pre-scripted [ 51 ]) and group sessions (yes or no). Participants in the group sessions were more engaged in SM and lost more weight than did those not offered group sessions; however, the group that received pre-scripted, modular FB had significantly greater weight loss than did the group that received the counselor-crafted FB while there was no consistent difference in their treatment engagement.…”
Section: Discussionmentioning
confidence: 99%
“…A recent pilot study that used a 2 × 2 factorial design provides some insights into FB (counselor-crafted vs pre-scripted [ 51 ]) and group sessions (yes or no). Participants in the group sessions were more engaged in SM and lost more weight than did those not offered group sessions; however, the group that received pre-scripted, modular FB had significantly greater weight loss than did the group that received the counselor-crafted FB while there was no consistent difference in their treatment engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 19 studies, 6 focused on diet [ 27 , 28 , 40 43 ], 14 focused on physical activity [ 24 26 , 36 , 41 , 43 52 ], 3 focused on sedentary behaviors [ 24 , 26 , 53 ], and 9 focused on weight management [ 24 , 27 29 , 40 43 , 51 ] (with some studies focusing on more than one of these behaviors) (Table 2 ). Outcomes for the different behaviors, however, varied widely between studies.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies included samples with a mean age between 30 and 50 [ 27 , 28 , 40 42 , 44 , 46 , 51 , 52 ] who were predominantly female [ 25 , 27 29 , 36 , 40 44 , 46 , 48 , 51 , 52 ] and White [ 26 29 , 41 , 42 , 44 , 46 , 51 , 53 ] (although ethnicity or race was not reported in 7 publications). Studies were conducted in the United States ( n = 10, 52.6%; [ 27 29 , 41 , 42 , 46 , 47 , 51 53 ], Brazil ( n = 1, 5.3% [ 43 ]), the Netherlands ( n = 1, 5.3% [ 40 ]), Finland ( n = 1, 5.3% [ 24 ]), Thailand ( n = 1, 5.3% [ 25 ]), China ( n = 1, 5.3% [ 45 ]), and the United Kingdom ( n = 4, 21.1% [ 26 , 36 , 44 , 48 ]. Study duration ranged from 2 days to 24 months, although most interventions ( n = 11) were shorter than 12 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, few past studies on behavioral weight management interventions have been conducted entirely remotely [ 28 , 105 , 106 ]. Two recent studies switched from an in-person to a fully remote format due to the COVID-19 pandemic and reported how outcomes differed by format: the weight loss maintenance study by Leahey et al [ 45 ] observed higher treatment attendance when done remotely versus in-person and excellent retention at study assessments for up to 18 months in both formats.…”
Section: Discussionmentioning
confidence: 99%